Bioremediasi Pestisida Metomil oleh Bakteri Pseudomonas aeruginosa - Ahmad Syafwan S Pulungan (CV.ITTC INDONESIA, 2023)
Methomyl is a pesticide from the carbamate group which is often used as an insecticide on agricultural land. The widespread use of methomyl pesticides on agricultural land will lead to the accumulation of residues that can contaminate the soil and waters. Exposure to these residues has a negative impact on human health because they can disrupt the work of the nervous system and are carcinogenic. Therefore, it is necessary to carry out bioremediation efforts by utilizing microorganisms that can degrade methomyl compounds. Pseudomonas aeruginosa can hydrolyze one of the carbamate pesticides, namely propoxur, to isoproxyphenol and methylamine which can be used as carbon and nitrogen sources for these bacteria. This study aims to test the ability of Pseudomonas aeruginosa to degrade metomyl pesticide. Pesticides that have been dissolved with water are mixed with Nutrien Agar media, then put in a petri dish. There were 3 treatments used, namely 2 ml, 5 ml, and 10 ml. Petri dishes that were not filled with methomyl pesticide were used as controls. Each control and treatment was repeated 2 times. The results showed that Pseudomonas aeruginosa grew the most in treatment 1, while treatment 3 was the least grown by Pseudomonas aeruginosa.